Phylogenetic differentiation and taxonomic consequences in the Saurodactylus brosseti species complex (Squamata: Sphaerodactylidae), with description of four new species - Javanmardi, Soheila; Vogler, Sven; Joger, Ulrich (Zootaxa, 2019)
We divide Saurodactylus brosseti into five species, based on molecular and morphological characteristics. Phylogenetic analysis of two mitochondrial markers (ND4 and 12S rRNA) reveals five separately evolving lineages (clades) in the S. brosseti species complex. Each can be assigned to a particular geographical range within the distribution area in Morocco: North, South, Anti-Atlas, East and Southeast. A dichotomous key for all species within the genus Saurodactylus is presented. Despite the high level of color pattern variation among and within the northern, southern, Anti-Atlas and eastern clades, the southeastern lineage shows a unique coloration which is not found in other clades. The ecological traits of the southeastern clade seem to differ from those of the other four lineages since it is basically associated with Acacia species. Like the relictual ecosystem characterized by these trees, it appears to be highly threatened by extinction.